Sharia Financial Accountability in the Property Sector: Implementation of Murabahah and Istishna’ Transactions - Azis, Indrawan; Haeruddin (Institut Bisnis dan Informatika Kesatuan, 2026)
The growth of the Islamic property industry in Indonesia requires accounting systems that not only comply with financial accounting standards but also align with Sharia principles. The complexity of cash and credit-based home sales transactions places accounting systems as a crucial instrument in ensuring transparency, accountability, and Sharia contract compliance. This study aims to examine the implementation of accounting systems for cash and credit home sales in Islamic property companies, focusing on revenue recognition, contract conformity, and internal control mechanisms. A qualitative case study approach was employed through in-depth interviews, observation, and document analysis. The findings reveal that the company has applied Sharia principles in determining cost structures, profit margins, and contract documentation. However, technical limitations persist, particularly the absence of formal written accounting policies and the lack of digitally integrated accounting systems. These findings emphasize the importance of standardized accounting policies, strengthened accounting information systems, and improved internal controls to support consistent and reliable Sharia-based accounting practices. This study contributes theoretically to Sharia accounting literature in the property sector and practically offers strategic recommendations for developers to enhance the quality of Sharia-based financial reporting.